2003
DOI: 10.1152/ajprenal.00426.2002
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HGF receptor gene expression by oxidative stress is mediated through the interplay between Sp1 and Egr-1

Abstract: Hepatocyte growth factor (HGF) receptor, the product of the c-metprotooncogene, is transcriptionally regulated by a wide variety of cytokines as well as extracellular environmental cues. In this report, we demonstrate that c-met expression was significantly suppressed by oxidative stress. Treatment of mouse renal inner medullary collecting duct epithelial cells with 0.5 mM H2O2inhibited c-met mRNA and protein expression, which was concomitant with induction of Egr-1 transcription factor. Ectopic expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
4
36
1
Order By: Relevance
“…By altering the interplay between Sp1 and Egr1, ZnPP could provide a means to manipulate gene expression relevant to tumorigenesis. Consistent with this hypothesis, gene expression of Met and Flt-1, all regulated by the interplay between Sp1 and Egr1 on the S/E site (40,47), are also inhibited by ZnPP in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By altering the interplay between Sp1 and Egr1, ZnPP could provide a means to manipulate gene expression relevant to tumorigenesis. Consistent with this hypothesis, gene expression of Met and Flt-1, all regulated by the interplay between Sp1 and Egr1 on the S/E site (40,47), are also inhibited by ZnPP in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Decreased Sp1 or enhanced Egr1 binding could lead to either transcriptional activation or repression, respectively. For example, Egr1 acts as a negative regulator and represses Sp1-mediated activation of some genes including protein-tyrosine phosphatase 1B, Met, Epstein-Barr virus C, and ␤ 1 -adrenergic receptor (40,42,44,45). In another circumstance, Egr1 competes with Sp1 protein for an overlapping region in the promoter of platelet-derived growth factor A and functions as a positive activator (46).…”
Section: Discussionmentioning
confidence: 99%
“…A protective role of Sp-1 was found during oxidative stress in brain neurons [9,14]. The regulation of gene expression by Egr-1 and Sp-1 transcription factors showed an interaction between them, since DNA-binding domains of these factors overlap [14,17]. We [14], and others [4,16], showed that Egr-1 and Sp-1 play an important role in pathogenesis of the inflammatory bowel diseases.…”
Section: Resultsmentioning
confidence: 99%
“…5A, cotransfection of EGR-1 increased NAG-1 promoter activity after TGZ treatment, whereas Sp1 expression resulted in the reduction of NAG-1 promoter activity compared with empty vector transfection. Functional interplay between Sp1 and EGR-1 has been described for a number of human gene promoters (49,(52)(53)(54). The cis-acting element required for Sp1/EGR-1 binding is usually represented by a GC-rich sequence (GC box).…”
Section: Discussionmentioning
confidence: 99%